Critical Study Of Chakras W.S.R. To Shaarir Vigyan In Ayurveda - Sharma, Komal; Saini, Subhash; Sharma, Jitendra Kumar (International Research Journal of Ayurveda & Yoga, 2020)
The chakars are center of energy thought to be nexus of metaphysical and /or biophysical energy residing in human body and provides passage for energy to enter and exit from body regulating all types of energy flow i.e., physical ,mental, emotional and spiritual and are connected to the network of psychic channels called ‘Nadis’ which corresponds to nerves but are more subtle .They are thought to be located along a central , vertical axis (Sushumna) at front of the body . Their interaction and manifestation of these chakras in the body is facilitated mainly by Nervous and Endocrine system. Ayurveda and Yoga consider five Vaayus - Apana, Prana, Samana, Vyana and Udana which are the vital air, active in all human beings responsible for existence & life. Thus, each chakra corresponds with specific vaayu. These chakras and glands believed to work together in co-ordination. Disturbances in the subtle energy of these chakras gets manifested in the various diseases which are likely associated with corresponding glands and organs. That is why these chakras have its own importance in Ayurveda. These chakras are six in number – Muladhara Chakra, Svadhishthana Chakra, Manipura Chakra, Anahata Chakra, Vishuddha Chakra, Ajna Chakra. Since Tantra Sharira is briefly described in textbooks of Rachana and kriya Sharira mostly on functional and spiritual aspects, so to highlight structural and the functional correlation of Chakras in view point of Ayurvedic Shaarir Vigyan this study was initiated.